Glycoprotein 90K, downregulated in advanced colorectal cancer tissues, interacts with CD9/CD82 and suppresses the Wnt/β-catenin signal via ISGylation of β-catenin. Issue 7 (25th June 2010) - Lee, Ji Hee; Bae, Jeong A; Lee, Jae Hyuk; Seo, Young-Woo; Kho, Dhong Hyo; Sun, Eun Gene; Lee, Song Eun; Cho, Sang Hee; Joo, Young Eun; Ahn, Kyu Youn; Chung, Ik Joo; Kim, Kyung Keun
Abstract : Background and aims: 90K, a tumour-associated glycoprotein, interacts with galectins and has roles in host defence by augmenting the immune response, but the serum 90K level was suggested to indicate poor prognosis in several cancers. The cellular mechanisms of 90K action on colorectal cancer (CRC) cell motility and its effect on CRC progression were investigated. Methods: The impact of 90K was analysed by combining cell cultures, in vitro assays, and immunohistochemistry. Results: Secreted 90K suppresses CRC cell invasion, but this action of 90K is masked through binding with extracellular galectins. A novel pathway is identified comprising a secretory 90K and a CD9/CD82 tetraspanin web; in this pathway, 90K interacts with CD9/CD82, suppresses the Wnt/β-catenin signal via a novel proteasomal-ubiquitination mechanism of β-catenin that is dependent on ISG15 (interferon-stimulated gene-15) modification (ISGylation) but not on glycogen synthase kinase 3β (GSK-3β) and Siah/Adenomatous polyposis coli (APC). In a syngeneic mouse colon tumour model, tumour growth and lung metastasis were increased with 90K knockdown. In colon tissues from stage IV human CRC and invading cancer cells of corresponding metastatic liver tissues, in which β-catenin and galectin expression was higher, immunostained 90K and CD9/CD82 were lower than in adjacent hepatic tissues or colon tissues from stage I. Conclusions: 90K itself has antitumour activity in CRC cells via suppression of Wnt signalling with a novel mechanism of ISGylation-dependent ubiquitination of β-catenin when it interacts with CD9/CD82, but is downregulated in advanced CRC tissues. The data suggest a strategy of strengthening this novel pathway with concomitant knockdown of galectins as a potential therapeutic approach to CRC progression.